2020
DOI: 10.1210/jendso/bvaa177
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of Polycystic Ovary Syndrome and the Gut Microbiome

Abstract: The etiology of polycystic ovary syndrome (PCOS) remains unclear although studies indicate that both genetic and environmental factors contribute to the syndrome. In 2012, Tremellen and Pearce proposed the idea that dysbiosis of the intestinal (gut) microbiome is a causative factor of metabolic and reproductive manifestations of PCOS. In the past five years, studies in both humans and rodent models have demonstrated that changes in the taxonomic composition of gut bacteria are associated with PCOS. Studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 102 publications
0
69
0
Order By: Relevance
“…In support of these findings, ovariectomy increases weight gain in both STND- and HFD-fed rats and is associated with changes in gut microbiota [ 59 ]. Similarly, in a PCOS mouse model, FMT from androgen-treated mice disrupts metabolic and endocrine health in germ-free recipients, whereas gut microbiota from control donors protects against metabolic dysregulation [ 60 , 61 , 62 ]. In a different study, diet-independent, ovariectomy-induced weight gain was not rescued by cohousing with intact mice, with the goal of transferring of gut microbiota [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of these findings, ovariectomy increases weight gain in both STND- and HFD-fed rats and is associated with changes in gut microbiota [ 59 ]. Similarly, in a PCOS mouse model, FMT from androgen-treated mice disrupts metabolic and endocrine health in germ-free recipients, whereas gut microbiota from control donors protects against metabolic dysregulation [ 60 , 61 , 62 ]. In a different study, diet-independent, ovariectomy-induced weight gain was not rescued by cohousing with intact mice, with the goal of transferring of gut microbiota [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the microbial community of adult patients with PCOS and healthy control, indicated by differences in βdiversity, have been identified in humans. 8,9,43,44 Adolescent girls (14-16 years old) with PCOS and obesity also showed differing βdiversity to girls with obesity but no PCOS. 45 In adult PNA rodents, the results of similar studies have been conflictingthere was no difference in PNA mice, whereas there was a difference in PNA rats.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies of the human gut microbiome have demonstrated lower αdiversity in premenopausal women with PCOS than in healthy women. 8,9,43,44 In addition, a recent study demonstrated that adolescent girls (14-16 years old) with PCOS and F I G U R E 1 1 Development of polycystic ovary syndrome (PCOS)-like phenotypes and changes in the gut microbiome in PNA offspring during their growth and development. A reproductive phenotype including disruption of the estrous cycle, histology typical of PCOS, and increased serum testosterone concentration were apparent at puberty in PNA female offspring.…”
Section: Discussionmentioning
confidence: 99%
“…( Hong et al., 2020 ) have discovered significant statistical differences in PCoA analysis of vaginal flora between PCOS and healthy people. However, there is also evidence suggesting that there is no statistically significant difference in beta diversity, for example, in intestinal flora and oral flora in PCOS patients ( Lindheim et al., 2016 ; Rizk and Thackray, 2021 ). This contradiction may exist for several reasons.…”
Section: Discussionmentioning
confidence: 99%